A Decision Model for Emergency Warehouse Location Based on a Novel Stochastic MCDA Method: Evidence from China. (16th November 2017) - He, Junkang; Feng, Chenpeng; Hu, Dan; Liang, Liang
Abstract : China is one of the disaster-prone countries in the world. Constructing a rapid and effective relief logistic system is important for disaster-responding at country level. Strategic prepositioning of emergency items, especially the decision of appropriate emergency warehouses location, has significant impacts on rapid disaster response to ensure sufficient relief supplies. The emergency warehouse location decision is a complex problem, where a wide variety of criteria need to be considered and the preference information of decision makers (DMs) may be imprecise or even absent. In this paper, we identify key effectiveness-oriented criteria used to evaluate the alternative emergency warehouse locations and make an attempt to propose a new multicriteria ranking method to solve the problem of inaccurate or uncertain weight information based on stochastic pairwise dominant relations and the pruning procedure of ELECTRE-II method. The proposed method extends the conventional ELECTRE-II method by incorporating inaccurate information and broadens its application to emergency warehouse location field. The feasibility and applicability of the proposed method are illustrated with a simulated example.